2020
DOI: 10.17645/mac.v8i2.2846
|View full text |Cite
|
Sign up to set email alerts
|

The Shorter the Better? Effects of Privacy Policy Length on Online Privacy Decision-Making

Abstract: Privacy policies provide Internet users with the possibility to inform themselves about websites’ usage of their disclosed personal data. Strikingly, however, most people tend not to read privacy policies because they are long and cumbersome, indicating that people do not wish to expend much (cognitive) effort on reading such policies. The present study aimed to examine whether shorter privacy policies can be beneficial in informing users about a social networking site’s (SNS) privacy practices, and to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 19 publications
0
7
0
4
Order By: Relevance
“…This might be because some users had never read or understood privacy policies on SM as found in previous studies (Jones and Soltren, 2005; O'Brien and Torres, 2012). Lengthy, uninteresting and complex presentations can be one of the main issues that make users reluctant to read or understand privacy policies (O'Bien and Torres, 2012; Meier et al , 2020). Additionally, cognitive studies have shown that the average human can only remember up to 10% of what they read (Naithani, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This might be because some users had never read or understood privacy policies on SM as found in previous studies (Jones and Soltren, 2005; O'Brien and Torres, 2012). Lengthy, uninteresting and complex presentations can be one of the main issues that make users reluctant to read or understand privacy policies (O'Bien and Torres, 2012; Meier et al , 2020). Additionally, cognitive studies have shown that the average human can only remember up to 10% of what they read (Naithani, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Schaub and colleagues [61] proposed a design space including four design dimensions (i.e., timing, channel, modality, control) that should be considered to design more usable and effective notices. Some research has shown that shorter privacy notices tend to be more effective in terms of readability and comprehension [49] and standardized privacy notices are more readable and better facilitate comparisons of privacy practices [2]. Gluck et al's study, however, found that extreme shortening of privacy notices did not improve readers' awareness of disclosed privacy practices, suggesting a potential length limit for short notices to be effective [35].…”
Section: Notices Beyond Privacy Policiesmentioning
confidence: 99%
“…Existe uma predominância dos signos metalinguísticos em relação aos demais, demonstrado pela desproporção no tamanho entre as metamensagens reconstruídas. Isso é resultado da política de dados do Instagram que é extensa, mesmo que políticas de privacidade maiores diminuam as chances de que os usuários as leiam e se informem [Meier et al 2020]. Ainda sobre os signos metalinguísticos, há uma falha na comunicabilidade quando se fala sobre os dados do usuário.…”
Section: Análise E Identificação Das Estratégias De Comunicaçãounclassified
“…Por fim, a política de dados do Instagram é extensa, o que é um problema, porque como já citado, políticas de privacidade maiores diminuem as chances de que os usuários a leiam e se informem [Meier et al 2020]. Ao longo de todo o documento também não foram identificadas informações sobre os riscos ou alternativas da coleta de dados do usuário, o que é necesário para o consentimento informado [Fjeld et al 2020].…”
Section: Considerações Finais E Conclusõesunclassified